Copper mediated C–H amination with oximes: en route to primary anilines. Issue 23 (24th May 2018) - Xu, Lin-Lin; Wang, Xing; Ma, Biao; Yin, Ming-Xing; Lin, Hai-Xia; Dai, Hui-Xiong; Yu, Jin-Quan
Abstract : Here we report an efficient Cu(i )-mediated C–H amination reaction with oximes as amino donors to introduce NH2 groups directly. Abstract : Here we report an efficient Cu(i )-mediated C–H amination reaction with oximes as amino donors to introduce NH2 groups directly. Various strongly coordinating heterocycles including quinoline, pyrimidine, pyrazine, pyrazole and triazole were tolerated well. The potential utility was further demonstrated in a late-stage modification of telmisartan (an antagonist for the angiotensin II receptor).